Relationship between intimate partner violence and depression symptoms in Turkish women: A cross-sectional study - Meltem Demirgöz bal; Özlem Aşcı (Preventive Care in Nursing and Midwifery Journal)
Background: Understanding the relationship between intimate partner violence (IPV) and depression/depressive symptoms is important in developing strategies to reduce the burden of depression and prevent IPV and its effects. Objectives: This study examined the relationship between IPV against women and depressive symptoms. Methods: This cross-sectional study conducted on 485 women from January to June 2023 in Turkey. Data were collected using a questionnaire assessing sociodemographic characteristics, Beck Depression Inventory (BDI), and Intimate Partner Violence against Women Scale (IPVAWS). Data were analysed using Student's t-test, ANOVA, Pearson correlation and multiple linear regression analysis in SPSS 24 software. Results: IPV and depression were found in 45.6% and 24.9% of the women, respectively. According to the multiple linear regression analysis, in which sociodemographic variables were controlled, one-unit increase in violence exposure scores increased the BDI scores by 0.49 times (p<0.001). Conclusion: Regardless of sociodemographic characteristics, beliefs about violence, and perceived social support, depressive symptomatology increased with increasing IPV exposure in women. Healthcare professionals should keep in mind the possible underlying exposure to intimate partner violence in women with depressive symptoms.